Pemanfaatan Limbah Oil Sludge Untuk Campuran Beraspal Jenis Lataston (Lapis Tipis Aspal Beton) Dengan Pengujian Marshall - Putra, Gia Nugraha; Wibisono, Gunawan; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Riau Province is well-known for its petroleum industry. The exploration and production activities of the industry produce waste products which potentially contaminate the environment. One of the petroleum waste is oil sludge. Based on the PP 101 2014, oil sludge is categorized as hazardous and toxic waste (B3) that must be processed before disposal. This study aims to investigate the potential of oil sludge as a partial replacement of asphalt in Hot Rolled Sheet-Wearing Course (HRS-WC). In this study the variation of oil sludge addition was 0%, 4%, 6% and 8% of the weight of asphalt. The addition of oil sludge decreased the optimum asphalt content (OAC) and increased the unit weight of the asphalt concrete mixture. This is caused by the fine grains contained in the oil sludge. Based on the Marshall characteristics test results, the maximum allowable content of oil sludge that could be used was 4% with 6.43% of OAC and 1,231 kg of average stability value which satisfied the specifications of Bina Marga 2010 Revision 3.Keyword : oil sludge, asphalt concrete, HRS-WC, Specification of Bina Marga 2010 Revision 3